การจัดการการใช้ดนตรีพื้นบ้านล้านนาเพื่อการส่งเสริมสุขภาพ ในโรงพยาบาลศูนย์ลำปาง อำเภอเมือง จังหวัดลำปาง - เฉลิมพล คุ้มศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Music has been applied for therapeutic purposes for a long time ago. To date, music is applied in every part of organization for both treatment and recreation, which influences physical and mental health. From previous studies, it was found that problems in applying music for health promotion of Lampang Center Hospital can be concluded as follows. The music was performed by Thai musical band. Those who played music were mostly personnel of Lampang Center Hospital including retired government officer and volunteers. At present, the band lacks of musicians and its members are decreasing. There is no responsible person, coordination and control. Moreover, the personnel do not have time to rehearse together. Therefore, the music is imperfect and tasteless. Furthermore, the instruments are not managed and maintained. Since the budget is insufficient, it is not successful and cannot achieve the goal of health promotion. Thus, one solution to alleviate anxiety of the patients and their relatives is to use Lanna folk music. This is because familiarity and relaxing feel when listening relieves the patients and their relatives. The important principle of health promotion is allowing the community to participate their own health. Therefore, playing folk music with participation of the community in the hospital is considered a method for health promotion. That is the application of Lanna folk music in the hospital for benefits and effectiveness for health promotion.